2016
DOI: 10.37558/gec.v9i0.289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación aeromicrobiológica del depósito del Centro de Documentación del Museo Nacional de la Música de Cuba

Abstract: El estudio tuvo como objetivos la caracterización de la microbiota aérea del local para evaluar el riesgo potencial de biomicrodeterioro de colecciones documentales de valor patrimonial. Se realizo a través del método de sedimentación y pruebas fisiológicas cualitativas que permitieron conocer la actividad biodeteriógena de la micobiota aislada, teniendo en cuenta el papel de los hongos en el biodeterioro colecciones de naturaleza orgánica. Se demostró una fuerte correlación positiva entre temperatura (T) y hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
3
3
1
3
Order By: Relevance
“…Although the fungal concentrations detected in the re-positories air did not exceed 500 CFU/m 3 , they considered intermediate [48] or moderate [49] , R-1 being the most contaminated repository during the three years studied. However, the concentrations obtained in this research were similar to those reported in previous studies performed in archives and libraries in other countries [41,47,50] and in Cuba both in naturally ventilated and air-conditioned environments [12,[51][52][53] . Likewise, these concentrations turned out to be low in relation to others obtained in foreign archives [48,54,55] .…”
Section: Discussionsupporting
confidence: 89%
“…Although the fungal concentrations detected in the re-positories air did not exceed 500 CFU/m 3 , they considered intermediate [48] or moderate [49] , R-1 being the most contaminated repository during the three years studied. However, the concentrations obtained in this research were similar to those reported in previous studies performed in archives and libraries in other countries [41,47,50] and in Cuba both in naturally ventilated and air-conditioned environments [12,[51][52][53] . Likewise, these concentrations turned out to be low in relation to others obtained in foreign archives [48,54,55] .…”
Section: Discussionsupporting
confidence: 89%
“…These genera coincide with those reported previously in environmental studies in Havana [15,[43][44][45] , also they prevailed in the supermarket Chong Chom in Thailand [46] , in the room of the Terracotta Warriors in Mausoleum of the First Emperor Qin in China [47] , in other archives, libraries and museums [48,49] as well as in the halls of Yale University (New Haven, Connecticut) where RF of occurrence of the genera Cladosporium, Penicillium and Aspergillus were 62, 40 and 26%, respectively [16] . These are considered normal contaminants of indoor environments and potentially allergenic, consistent with that reported previously [16] .…”
Section: Resultssupporting
confidence: 91%
“…Los representantes de Aspergillus spp. en los tres depósitos constituyeron una parte considerable de la micobiota aérea viable si se tienen en cuenta que las DR fueron superiores al 18%, que en todos los locales se detectaron al menos 6 géneros fúngicos y que en términos de concentración, se ubicó siempre entre los tres géneros más representados con un máximo de 45 UFC -3 en MNBA Aspergillus en todos los casos, cuestión que está relacionada con la influencia de dicho factor en la presencia y viabilidad de sus propágulos (Rodríguez et al, 2014). En tanto la T y las concentraciones de propágulos mostraron una correlación baja negativa (R = -0,4878 para P ≤ 0.05) (figura 1B, C y D).…”
Section: Análisis Ecológicounclassified
“…En tanto la T y las concentraciones de propágulos mostraron una correlación baja negativa (R = -0,4878 para P ≤ 0.05) (figura 1B, C y D). La T suele ser influyente en la dinámica de la micobiota en el aire interior, sin embargo al parecer ejerce un efecto secundario al actuar sobre otros factores como la HR y las corrientes de aire (Rodríguez et al, 2014). Por otra parte, se ha reportado la prevalencia de especies de Aspergillus en ambientes interiores con alto nivel de empolvamiento y falta de ventilación, elementos que propician la existencia de reservorios esporales (Molina…”
Section: Análisis Ecológicounclassified
See 1 more Smart Citation